Recursos digitales en el aula invertida en estudiantes de bachillerato en ciencias, Unidad Educativa 10 de Agosto - De la Cruz Rocafuerte, Erika Jacinta (2023)
The general objective of this study was to analyze the use of digital resources in the inverted classroom in high school students in science, Educational Unit 10 de Agosto, for which a basic type of research was used, the same that will use a descriptive methodology, documentary, which is oriented to the development of a quantitative approach, in a non-experimental design, The population for the present research is centered on 128 students, opting for a non-probabilistic sample resulting in 96 students to participate in the statistical development, the technique used for the collection of data and information was the survey and the instrument was the questionnaire, which for the present research consisted of 11 questions. The results showed that 88% of the students were willing to include an inverted classroom methodological system with the inclusion of educational platforms and software for the development of the teaching-learning process. Concluding that the inclusion of these digital resources allows a better development of the ludic activities in class, reason why the inverted classroom methodology would serve as a catalyst for the fulfillment of the institutional objectives and a motivator to improve the current educational system.